The Effect of Supply Chain Integration on the Effectiveness of Batik Product Development Design at the Tuban Center - Kalista, Anggia (Dinasti Publisher, 2025)
This study aims to determine whether there is a significant influence between supply chain integration and the effectiveness of batik product design development in the Batik Center of Tuban. This research is grounded in the importance of interconnectedness among supply chain actors to enhance the quality and competitiveness of sustainable local product designs. A quantitative approach was employed using an ex post facto design, meaning data were collected after the events had occurred without any experimental manipulation. The sample consisted of the entire population, totaling 60 batik industry participants. Data analysis was conducted with the assistance of SPSS version 22. The statistical results indicate that supply chain integration significantly affects the effectiveness of design development. The stronger the integration—such as in information sharing, production process synchronization, and collaboration between suppliers and producers—the more optimal the product design outcomes. These findings highlight the vital role of strategic collaboration across the entire supply chain in enhancing the competitiveness of batik products.